MIRABEGRON VS ALPHA BLOCKERS IN MEDICAL EXPULSIVE THERAPY IN DISTAL URETERIC CALCULUS (The Research of Medical Science Review, 2025)
Background: Medical Expulsive Therapy (MET) enhances the rapid removal of stones with ureteral blockage avoidance and ureteral colic relief. Mirabegron and Tamsulosin both have been helpful as MET for ureteric calculus (UC). Objective: Method: To compare the effectiveness of Mirabegron and Tamsulosin in distal ureteral stone expulsion (SE) in patients presenting with distal UC. This is a randomized controlled trial conducted at the Urology Department of Indus Hospital and Health Networks, Korangi campus, Karachi from April 2024 to February 2025. Participants were randomly divided into groups A and B. Patients in group A received Mirabegron 50mg, Drotaverine 40mg, and Diclofenac 50mg. Group B patients received Tamsulosin 0.4mg, Drotaverine 40mg, and Diclofenac 50mg. After 4 weeks, Computed Tomography (CT) was done to evaluate the presence or absence of ureteral stone. The chi-square test was employed to compare the effectiveness between the two groups with a p-value of ≤0.05 considered statistically significant. Results: A total of 94 patients (47 in each group) were enrolled in this study with an average age of 31 years. SE was observed in 27 patients (52.9%) who received tamsulosin and 24 patients (47.1%) who received Mirabegron treatment. No major effect on SE was seen in either treatment group. Conclusion: More studies with bigger sample numbers and a wider range of demographics could help confirm these results and investigate Mirabegron's long-term effects on ureteral SE. Ultimately, this study emphasizes how critical it is to keep researching and contrasting different medical treatments to improve patient care for urolithiasis management.